2016
DOI: 10.3389/fpsyt.2016.00147
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Disorder, Adverse Childhood Events, and Buccal Cell Telomere Length in Elderly Swiss Former Indentured Child Laborers

Abstract: Posttraumatic stress disorder (PTSD) is associated with increased risk for age-related diseases and early mortality. Accelerated biological aging could contribute to this elevated risk. The aim of the present study was to assess buccal cell telomere length (BTL) – a proposed marker of biological age – in men and women with and without PTSD. The role of childhood trauma was assessed as a potential additional risk factor for shorter telomere length. The sample included 62 former indentured Swiss child laborers (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 50 publications
(72 reference statements)
3
32
0
Order By: Relevance
“…The remaining studies adopted retrospective ACE reporting measures with adult participants. The most common psychiatric conditions considered in the studies were major depressive disorder [11,[21][22][23][24][25] and borderline personality disorder [23,24,[26][27][28][29], followed by post-traumatic stress disorder [8,23,30,31]. Two studies considered eating disorders [26,32].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining studies adopted retrospective ACE reporting measures with adult participants. The most common psychiatric conditions considered in the studies were major depressive disorder [11,[21][22][23][24][25] and borderline personality disorder [23,24,[26][27][28][29], followed by post-traumatic stress disorder [8,23,30,31]. Two studies considered eating disorders [26,32].…”
Section: Resultsmentioning
confidence: 99%
“…Six demonstrated a shortened telomere length correlating with ACEs [8][9][10][11][12] and one showed a link between shortened telomeres and ACE exposure which was not sustained over time [22]. One paper showed no link between telomere length and exposure [30]. Tyrka and colleagues reported shorter telomere length in adults exposed to ACEs, even after controlling for confounders [10].…”
Section: Telomere Studiesmentioning
confidence: 99%
“…For example, parental separation in early childhood alone was not be enough to predict telomere erosion in a sample of n ¼ 1486 individuals (n ¼ 215 with childhood separation). [71][72][73] Variability in TL measurement methods across studies, ranging from different DNA extraction procedures [79] to varied TL quantifications, [80] may also account for the inconsistencies observed. [39,78] As such, TL exhibits a similar pattern to health risk after ACE exposure and may help explain the dose-response relationship between number of exposures and health burden.…”
Section: How Does Resilience Affect Biologic Findings After Early Lifmentioning
confidence: 99%
“…[70,71] In a sample of elderly Swiss former indentured child laborers, there was no relationship between childhood adversity and buccal TL. [72] Similarly, an analysis of the Netherlands Study of Depression and Anxiety cohort initially reported that childhood trauma was not associated with shorter TL. [73] However, a more recent analysis of this cohort found a significant relationship between childhood trauma and the 6 year telomere attrition rate despite there still being no association between childhood trauma and TL.…”
Section: How Does Resilience Affect Biologic Findings After Early Lifmentioning
confidence: 99%
See 1 more Smart Citation